The Decreased Cloud Cover Dominated the Rapid Spring Temperature Rise in Arid Central Asia Over the Period 1980–2014 - Gongxin Wang; Xiuliang Yuan; Changqing Jing; Rafiq Hamdi; Friday Uchenna Ochege; Ping Dong; Yuqing Shao; Xueyan Qin (Geophysical Research Letters)
Abstract Central Asia (CA) has experienced a faster temperature rise than the global land over the past decades. However, the role of regional/global drivers and their associated underlying biophysical mechanisms is poorly explored. Here, we combined observations and model simulations to show that the rapid warming in CA was overwhelmingly contributed by rapid spring warming (i.e., 49.23%). The decrease of cloud cover (CLD) was the main driver of spring warming in CA, leading to the surface receiving more solar radiation, consequently heating the surface air temperature, and contributing almost 40.79% to the spring warming. Besides, the strengthening of sea level pressure states results in continuous subsidence of vertical motion over CA, which was unfavorable for cloud formation. Our study will deepen our understanding of the climate evolution in the arid CA.